Public speaking skills of public relations at statistics of West Java Province - Saleh, Andri; Setianti, Yanti; Budiana, Heru Ryanto (Universitas Padjadjaran, 2024)
Background: Statistics Indonesia (BPS) is one of the government agencies that always engage with the community through, for example, censuses, surveys, and dissemination of statistical data. For that reason, the role of Public Relations at BPS is certainly needed. However, the organizational structure of Public Relations does not exist at BPS provincial and regency/city levels. The role of Public Relations at BPS provincial and regency/city levels is carried out by employees that are appointed based on policies through Public Relations Decree. Purpose: This study aims to examine public speaking skills possessed by the public relations staff of BPS Province and Regency/City of West Java. Methods: This study employed a descriptive quantitative approach. The sample used was a saturated sample of 79 people who were appointed as Public Relations of BPS Province and Regency/City of West Java in 2022. Results: The results showed that as many as 97.46 percent of Public Relations of BPS Province and Regency/City of West Java did not earn a degree from public relations background and only 37.97 percent had attended a Public Relations training. However, the public speaking skills of public relations staff of BPS Province and Regency/City of West Java were reported as “Good” category, both in general and in terms of gender, age, and education. Conclusion: This “Good” category result is argued to be caused by habituation to public speaking activities through meetings, committee activities, and training instructors. Implications: BPS Province and Regency/City of West Java should hold training activities, courses, and workshops on the topic of Public Relations routinely to improve the skills of Public Relations.